Differential Effects of Chlorhexidine Skin Cleansing Methods on Residual Chlorhexidine Skin Concentrations and Bacterial Recovery. (1st March 2018) - Rhee, Yoona; Palmer, Louisa J.; Okamoto, Koh; Gemunden, Sean; Hammouda, Khaled; Kemble, Sarah K.; Lin, Michael Y.; Lolans, Karen; Fogg, Louis; Guanaga, Derek; Yokoe, Deborah S.; Weinstein, Robert A.; et al.
Abstract : BACKGROUND: Bathing intensive care unit (ICU) patients with 2% chlorhexidine gluconate (CHG)–impregnated cloths decreases the risk of healthcare-associated bacteremia and multidrug-resistant organism transmission. Hospitals employ different methods of CHG bathing, and few studies have evaluated whether those methods yield comparable results. OBJECTIVE: To determine whether 3 different CHG skin cleansing methods yield similar residual CHG concentrations and bacterial densities on skin. DESIGN: Prospective, randomized 2-center study with blinded assessment. PARTICIPANTS AND SETTING: Healthcare personnel in surgical ICUs at 2 tertiary-care teaching hospitals in Chicago, Illinois, and Boston, Massachusetts, from July 2015 to January 2016. INTERVENTION: Cleansing skin of one forearm with no-rinse 2% CHG-impregnated polyester cloth (method A) versus 4% CHG liquid cleansing with rinsing on the contralateral arm, applied with either non–antiseptic-impregnated cellulose/polyester cloth (method B) or cotton washcloth dampened with sterile water (method C). RESULTS: In total, 63 participants (126 forearms) received method A on 1 forearm (n=63). On the contralateral forearm, 33 participants received method B and 30 participants received method C. Immediately and 6 hours after cleansing, method A yielded the highest residual CHG concentrations (2500 µg/mL and 1250 µg/mL, respectively) and lowest bacterial densities compared to methods B or C ( P <.001). CONCLUSION: In healthy volunteers, cleansing with 2% CHG-impregnated cloths yielded higher residual CHG concentrations and lower bacterial densities than cleansing with 4% CHG liquid applied with either of 2 different cloth types and followed by rinsing. The relevance of these differences to clinical outcomes remains to be determined. Infect Control Hosp Epidemiol 2018;39:405–411